International perspective on healthcare provider gender bias in musculoskeletal pain management: a scoping review protocol - Katherine Fisher Wilford; Maria Jesus Mena-Iturriaga; Margaret Vugrin; Macarena Wainer; Phillip S Sizer; Gesine Hendrijke Seeber (BMJ Open)
Introduction Chronic pain affects millions of individuals worldwide. Healthcare provider gender bias in the management of these individuals has societal and individual ramifications. Yet, a thorough and comprehensive literature summary on this topic is lacking. Therefore, this study aims to systematically: (1) identify and map the available scientific and grey literature as it relates to healthcare provider gender bias in the assessment, diagnosis and management of (chronic) musculoskeletal pain and (2) identify current gaps that necessitate further research.Methods and analysis This scoping review will be conducted in accordance with recent guidelines, and the results will be reported via the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews. The following databases will be searched: PubMed (National Library of Medicine), Embase (Elsevier), Scopus (Elsevier), CINAHL Complete (Ovid), Academic Search Complete (Ebscohost), Pre-Prints Database (National Library of Medicine) and Rehabilitation Reference Center from inception to August 2022. Additionally, relevant grey literature will be identified. All screening will be done by two independent reviewers during two stages: first title/abstract screening followed by full-text screening. Data will be extracted from the bibliometric, study characteristics, and pain science families of variables. Results will be descriptively mapped, and the frequency of concepts, population, characteristics and other details will be narratively reported. Additionally, results will be presented in tabular and graphical form.Ethics and dissemination As this study will neither involve human subject participation nor utilisation of protected data, ethical approval is not required. This study’s methodological approach follows current recommendations. Study findings will be disseminated through conference presentations and international peer-review journal publication. In addition, infographics available in English, Spanish and German will be disseminated.Registration details This project will be registered in Open Science Framework prior to data collection.